Choreographing Sapayung Dance for Children at Mutiara Minang Studio in Padang City - Tri Septiana Ratmaniarti; Darmawati (Universitas Negeri Padang, 2024)
This research aims to reveal and describe the choreography of Sapayung Dance specifically created for children at Mutiara Minang Studio in Padang City. The type of research is qualitative with descriptive method. The research instrument is the researcher himself by using tools such as stationery, books, mobile phones, digital cameras. The research data are primary data and secondary data. Data collection techniques are done by means of literature study, observation, interviews, documentation. The steps of analysing data are data collection, data reduction, data presentation and conclusion drawing. The results showed that this Sapayung dance was created with good choreographic principles and consists of choreographic elements which include theme, movement, floor design, dynamic design, music, property and costumes. The theme of Sapayung dance is for entertainment. In the musical design of this Sapayung dance using techno music. Sapayung dance has an atmosphere of excitement. The process of Sapayung dance starts from the idea that the choreographer has and is poured into the form of motion that comes from the creativity of the choreographer.